Different formulations of entomopathogenic nematodes for the control of false codling moth: Different formulated EPNs for the control of false codling moth - Malan, Antoinette Paula; Schlesinger, Subrina; Dunn, Murray David; Ritter, Carla; Motloung, Bennie; Klumperman, Bert (South African Journal of Enology and Viticulture, 2026)
Most of previous research on entomopathogenic nematodes (EPNs) in South Africa has focused on the use of EPNs against false codling moth (Thaumatotibia leucotreta, FCM) in citrus orchards. However, in recent years, it has become evident that this pest has shifted to other hosts, with table grapes becoming an important concern in terms of export. No control measures in viticulture are currently directed at the soil-dwelling stages of FCM, presenting a niche that EPNs have the potential to fill. Despite significant progress in formulation techniques for EPNs, challenges such as limited shelf-life and microbial contamination remain problematic. In this study, locally sourced isolates of Steinernema yirgalemense and Heterorhabditis bacteriophora were produced through in vitro liquid culture and the shelf-life and pathogenicity of different formulations were assessed, along with the use of Xenorhabdus indica bacterial metabolites as a possible strategy to reduce microbial contamination. Results demonstrated that carboxymethylcellulose (CMC) and cellulose nanofibril (CNF) gel formulations enhanced the longevity of IJs, while maintaining virulence over time. Soil bioassays showed no differences in FCM larval pathogenicity between the formulated and unformulated nematodes, with an infection rate of > 90% after 48 h.